Gender Issue in COVID-19 Pandemic - Giri, Santoshi; Khadka, Sitaram; Ranabhat, Sushma; Agha, Mariam (Journal of Karnali Academy of Health Sciences, 2020)
Since the first outbreak, COVID-19 has manifested itself as a serious public health threat with severe social and economic implications. Gender is an essential component that requires special attention and action in such crisis. This review is aimed at finding the gender-related issues amid COVID-19 pandemic that need to be considered and help stimulate related stakeholders to devise effective policies and actions.Health, socio-economical and education, all domains of gender are viciously affected by this pandemic. Though men and women have the same prevalence, men with COVID-19 are more at risk of worse outcomes and death. Even though the direct impact of disease is observed significantly high in men, the secondary socio-economic impact is catastrophic in women and girls considering their status in society as they are systemically oppressed and vulnerable group of population. The pandemic will have a prolong effect on socioeconomic dynamics. Hardly achieved milestones on gender equality reached low, which will take long to bounce back. From this crisis, government and policy makers should take a lesson and formulate public health policies and measures to contain the epidemic that takes account of gender and its interactions with all areas of inequality.